Development of Aloe Vera based Gel Polymer Electrolyte for Dye Solar Cells Application - YUHARMON, NUR AMINATON SUFIA (2021)
Dye solar cell (DSSC) with liquid electrolyte exhibits higher efficiency greater than 11%, but it suffers from loss of electrolyte due to the leakage leading to the limitation for long-term usage. This poses a major challenge to the development of flexible dye solar cell. Therefore, gel polymer electrolyte has been introduced because of easy sealing process, resulting in minimal loss of electrolyte for enhanced durability. Nowadays, organic materials are being used in a wide range of solar cells application because of their properties, environmentally safe and low cost. Unfortunately, they cannot act as the electrolyte on their own. They should be mixed with other low molecular weight polymer gelator and gelled with liquid electrolyte to form gel polymer electrolytes. In this research study, Aloe Vera gel extracted from the aged Aloe Vera leaves has been used as an electrolyte in DSSC. For comparative study, other gel polymer electrolytes used are mannose, agarose and carboxymethyl-cellulose (CMC). Soxhlet extraction method was selected to extract the polysaccharides in Aloe Vera gel by using two types of organic solvent, namely ethanol and hexane and also their combination (ethanol: hexane) at the ratio of (7:3), (5:5) and (3:7), respectively. Extraction yield for Aloe Vera gel from the mixture of ethanol and hexane with the ratio of (7:3) possess the highest value of polysaccharides at 35.01 wt%. This Aloe Vera gel was then used to develop new gel polymer electrolyte by blending with CMC, reduced graphene oxide and iodide/tri-iodide organic electrolyte solution. This composite electrolyte was incorporated together with the photoelectrode and the dye in an assembly of test cell for four different active areas, namely 1.00, 0.70, 0.50 and 0.40 cm2. The fabricated test cells (active area of 0.40 cm2) incorporated with AVG-Ethanol-Hexane (7:3)/CMC-rGO- Iˉ/I₃ˉ gel polymer electrolyte, exhibited the highest conversion efficiency (η) of 0.84%. However, it is still lower compared to mannose (2.35%), agarose (3.55%) and CMC (5.76%) gel polymer electrolyte, due to the low percentage of the extracted polysaccharides. Successful development of gel polymer electrolyte from Aloe Vera gel with high electron density has reduced the recombination rate (81.19 s-1), leading to an increase in the electron lifetime (1.83×10-3 s), which is critical for the improvement of efficiency. This implies that this new gel polymer electrolyte has a potential to increase the efficiency of DSSCs if 100% polysaccharides can be extracted from Aloe Vera.